Radiation Exposure to the Patient During Diagnostic Coronary Angiogram at Dhulikhel Hospital - Humagain, S; Maharjan, R; Koju, R (Kathmandu University Medical Journal, 2015)
Background Radiation is a necessary evil in Coronary Angiogram. The Interventional Cardiology procedure provides huge benefit to the patient but at the cost of radiation. There is evidence of cumulative effect of radiation. Therefore it is essential to keep the radiation dose as minimum as possible. Objective The aim of this study is to find out radiation exposed to the patient undergoing diagnostic coronary angiogram. Method A retrospective study was done. Those patients who underwent diagnostic coronary angiogram were selected for the study. There were total of 166 patients. Radiation exposure in terms of fluoroscopy time in minute and dose area product (DAP) in Gy.cm2 was recorded. Result Out 166 patients 92 were male and 74 female. Age range was from 39 to 79 years with mean age 58.13±9.14. Amount of contrast used was in range of 30 to 100 ml with mean of 45.54±14.06. Range of fluoroscopy time was 2.60 to 37.00 minutes with mean 11.38±6.80. Mean fluoroscopy time in male was 10.92±5.82 minutes and in females it was 11.92±7.68 minutes, with p 0.331. The range of DAP was 11.00 Gy.cm2 to 106.00 Gy.cm2 with mean 40.73±23.58 Gy.cm2. The mean DAP in male and female was 38.77±23.26 Gy.cm2 and 43.16±23.90 Gy.cm2 respectively with p 0.234. Conclusion From this study we can conclude that the radiation exposure to our patient undergoing coronary angiogram is similar to the international values in terms DAP but more in terms of fluoroscopy time. When males and females compared there is no difference. Kathmandu University Medical Journal Vol.13(1) 2015; 61-63